Immunological effects of CD19.CAR-T cell therapy in systemic sclerosis: an extended case study - Claus, Maren; Freitag, Merle; Ewald, Meike; Rodon, Lea; Deicher, Franca; Watzl, Carsten; Kolb, Philipp Leonhard; Lorenz, Hanns-Martin; Schmitt, Michael; Merkt, Wolfgang (Arthritis Research & Therapy, 2024)
Objective: The high potential of CD19.CAR-T cells to treat autoimmune diseases such as Systemic Sclerosis (SSc) supposedly relies on the disappearance of autoantibodies. Here we investigated effects of CAR-T cells on the innate immune system which is an important contributor to pathology in SSc. Methods: Longitudinal analysis of peripheral blood mononuclear cells from an Scl70 + SSc patient treated with CAR-T cells sampled over 18 months by 29-color spectral flow cytometry, in vitro experiments using sera from patient cohorts. Results: In the patient treated with CAR-T cells, the substantial clinical improvement was paralleled by dynamic changes in innate lymphoid cells, namely Fcγ-receptor IIIA-expressing natural killer (NK) cells. NK cells adopted a more juvenile, less activated, and less differentiated phenotype. In parallel, the potency of serum to form Scl70-containing immune complexes that activate Fcγ-receptor IIIA decreased over time. These observations suggested a mechanistic link between reversal of adaptive autoimmunity and recovering Fcγ-receptor IIIA-expressing innate immune cells after CAR-T cell therapy via regressing immune complex activity. Experiments with sera from the non-CAR-T-treated SSc cohort confirmed that Scl70-containing immune complexes activate Fcγ-receptor IIIA-expressing NK cells in a dose-dependent manner, substantiating the relevance of this link between adaptive and innate immunity in SSc. Conclusion: This report describes for the first time the phenotypic recovery of innate Fcγ-receptor-expressing cells in an SSc patient treated with CAR-T cells. Decreasing autoantibody levels associated with a reduced ability to form functional immune complexes, the latter appearing to contribute to pathology in SSc via activation of Fcγ receptor IIIA + cells such as NK cells.
Gesehen am 21.03.2025